Deterministic assessment of the ecological vulnerability of coastal freshwater canals: A perspective on social awareness and conservation - NAJMUS SAKIB KHAN; MD. SAIFUL ISLAM; JABER BIN ABDUL BARI; MAEEN UDDIN; IRINA MASHKOVA; ANASTASIYA KOSTRYUKOVA; VIKTOR TROFIMENKO (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Khan NS, Islam MS, Bari JBA, Uddin M, Mashkova I, Kostryukova A, Trofimenko V. 2023. Deterministic assessment of the ecological vulnerability of coastal freshwater canals: A perspective on social awareness and conservation. Biodiversitas 24: 5179-5188. Inland freshwater canals are formed by geomorphological evolutions or artificially for communal welfare. The freshwater canal ecology differs mainly from rivers, estuaries, and the ocean for salinity variables, nutrient concentrations, morphological structure, and unique flora and fauna distribution. These canals and their aquatic organisms are very sensitive to surface runoff and direct sewage pollution. Thus, these freshwater canals become threats to society in case of contamination. The current study focused on the water quality, microalgae, and zooplankton communities in two renowned canals: Basurhat (BH) canal and Dotterhat (DH) canal in coastal Noakhali, Bangladesh. The study attempted to demonstrate these canals' aquatic and ecological status by evaluating plankton distribution and some important water quality parameters. Furthermore, a classic Palmer's algal organic pollution Index and wetland zooplankton Index were applied to determine the water quality according to species assemblages of freshwater algae and zooplankton, respectively. The present study identified 27 phytoplankton genera from Bashurhat Canal and 21 from Datterhat Canal. At the same time, 16 genera of zooplankton were observed with 2,269.09±52.12 ind/L and 4,588.54±40.79 ind/L from Bashurhat Canal and Datterhat Canal, respectively. The water quality differed from Bashurhat Canal and Datterhat Canal, where the highest temperature was found at Bashurhat Canal at 23.55±0.15°C and the lowest was 22.6±0.1°C. Moreover, the highest and lowest temperature was found from Datterhat Canal as 29.8±0.9°C and 29.67±0.78°C respectively. The highest transparency (cm), Dissolve Oxygen (mg/L), alkalinity (mg/L), free carbon dioxide (mg/L), ammonia (mg/L) and TSS (mg/L) were found as 29±1.0, 1.25±0.25, 58.76±0.26, 59.25±0.66, 8.25±0.25, 2.25±0.05 and the lowest were found 20.5± 0.5, 0.75±0.25, 27.73±0.49, 11.28±0.69, 8.15±0.15, 2.2±0.1 in Bashurhat Canal. Additionally, the highest transparency (cm), Dissolve oxygen (mg/L), alkalinity (mg/L), free carbon dioxide (mg/L), ammonia (mg/L), and TSS (mg/L) were found as 15.75±0.25, 1.85±0.50, 53.96±0.5, 55.09±0.8, 8.1±0.1, 4.0±0.1 and the lowest were identified 14.5± 0.5, 1.25±0.25, 23.1±0.4, 49.23±0.38, 7.65±0.50, 2.54±0.75 in Datterhat Canal. The study results indicate the deterioration of water quality in urbanized canals and that aquatic ecosystems face many long-term anthropogenic pressures. The current canal state requires measures to restore them. In addition, there is a need for strict control over the discharge of waste and pollutants from residential areas, fish markets, and hospitals.